Bacterial meningitis: an update of new treatment options. Issue 11 (2nd November 2015) - Nau, Roland; Djukic, Marija; Spreer, Annette; Ribes, Sandra; Eiffert, Helmut
Abstract : The outcome of bacterial meningitis critically depends on the rapid initiation of bactericidal antibiotic therapy and adequate management of septic shock. In community-acquired meningitis, the choice of an optimum initial empirical antibiotic regimen depends on the regional resistance patterns. Pathogens resistant to antibacterials prevail in nosocomial bacterial meningitis. Dexamethasone is recommended as adjunctive therapy for community-acquired meningitis in developed countries. In comatose patients, aggressive measures to lower intracranial pressure <20 mmHg (in particular, external ventriculostomy, osmotherapy and temporary hyperventilation) were effective in a case–control study. Although many experimental approaches were protective in animal models, none of them has been proven effective in patients. Antibiotics, which are bactericidal but do not lyse bacteria, and inhibitors of matrix metalloproteinases or complement factor C5 appear the most promising therapeutic options. At present, vaccination is the most efficient method to reduce disease burden. Palmitoylethanolamide appears promising to enhance the resistance of the brain to infections.